KEBERKESANAN KAEDAH KIJO MEMBANTU MURID TAHUN 3 HISYAM DI SEKOLAH RENDAH AGAMA BERSEPADU KLUANG MENGATASI MASALAH PENGUASAAN KONSEP DARAB - Janjam, Noor Afida Zunaiza; Ibrahim Mukhtar, Marina (Online Journal for TVET Practitioners, 2018)
This research was conducted to test the effectiveness of the methods of KIJO against 38 year 3 Hisyam in Sekolah Rendah Agama Bersepadu Kluang against the concept of multiplication. This method involves the representation of the letters K, I, J and O with math multiplication symbol in verse represents the object to be in multiplication. this research provides an opportunity for educators to assess its effectiveness against the understanding of the concept of multiplication pupils, detect tendencies interest pupils in learning the concept of multiplication. Pre and post test and questionnaire has been conducted to collect data. Data analyzed using excel software. Results of analysis showed that a variety of methods to make a practice of learning in learning the concept of multiplication on the rise and can assist students in mastering the concept of multiplication. This study shows that the existence of a significant relationship of the effectiveness of the methods of KIJO undertaken. In this study, indicators related to the effectiveness of learning multiplication topic was influenced by the improved performance of students, application of basic concepts through effective method and the interest of students towards the subjects.